Sporadic Rectocolic Polyps Prevalence and Management - Mrabti, Samir; Sair, Asmae; Benhamdane, Ahlame; Addajou, Tarik; Berrida, Réda; Sentissi, Sara; Koti, Ilham; Rouibaa, Fedoua; Benkirane, Ahmed; Seddik, Hassan (Journal of Coloproctology, 2022)
Objective To evaluate the prevalence of polyps and their treatments.Materials and Method This is a retrospective study conducted in our department over 20 years and 3 months between January 2000 and March 2021. All patients with colorectal polyps who underwent endoscopic resection were included. We evaluated the resection techniques and the management of complications.Results The total number of patients was 273, with a mean age of 57.26 ± 14.058 (18–90) and a M/W sex ratio of 2. The prevalence was 3.35% and the mean number of polyps was 1.33 ± 0.69. The most frequent symptoms were rectal bleeding (23.5%) and constipation (12.1%). The median size was 6 mm (4–12 mm). The left colonic location was the most frequent site (43%). All polyps were classified according to the Paris classification, with a predominance of sessile polyps in 45.75%, followed by pedunculated polyps, representing 42.4%. Endoscopic resection was performed either by biopsy forceps, polypectomy, or mucosectomy in 30.2%, 27.4%, and 25.4% of cases, respectively. Our study noted immediate bleeding in 1.5% of cases, and no perforations or late complications. All complications were treated endoscopically, and no patient required blood transfusion or surgical intervention.Conclusion Endoscopic resection of rectocolic polyps is the ideal treatment for these lesions. In our department, the prevalence was 3.35%, the most used resection techniques were forceps resection and polypectomy, and the complication rate was 1.5%.
Keywords: polyp; colonoscopy; prevalence; resection; complications